Digital copies of «Instructive gospel» in manuscripts and early printed tradition - A. J. Borodikhin; A. V. Shabanov (Библиосфера, 2012)
The article introduces the results of works on digitalizing of outstanding old Russian manuscripts and early printed books which are carried out in the Rare book and Manuscript Department of SPSTL of SB RAS. The novelty and currency of this area in the study of Russian medieval book culture is determined by the factor of searching archaeographical work. Their presentation in the series «Book monument of Siberia» answers the urgent tasks of broadening the source base for scientific developments in the area of humanitarian studies.